2015
DOI: 10.1590/0103-6440201300416
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light Source, Thermocycling and Silane on the Shear Bond Strength of Metallic Brackets to Ceramic

Abstract: The objective of this study was to evaluate the effects of different light sources, thermocycling and silane on the bond strength of metallic brackets to ceramic. Cylinders of feldspathic ceramic were etched with 10% hydrofluoric acid for 60 s. Half of the cylinders (Groups 1 to 4) received two layers of silane. Metallic brackets were bonded to the cylinders using Transbond XT and divided into 8 groups (n=20), according to light source (Radii Plus LED - 40 s; Groups 1, 2, 5 and 6 and XL 2500 halogen light - 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The results indicated that the second hypothesis was not accepted. The results of the present work are in agreement with those of previous studies, which found significant difference in bond strength values when the specimens were submitted to thermal cycling 2,4 . On the other hand, other studies are not in agreement showing no significant difference for bond strength of specimens submitted to thermal cycling 11,16 .…”
supporting
confidence: 93%
See 4 more Smart Citations
“…The results indicated that the second hypothesis was not accepted. The results of the present work are in agreement with those of previous studies, which found significant difference in bond strength values when the specimens were submitted to thermal cycling 2,4 . On the other hand, other studies are not in agreement showing no significant difference for bond strength of specimens submitted to thermal cycling 11,16 .…”
supporting
confidence: 93%
“…However, bonding orthodontic brackets to ceramic surface needs special care because they can exhibit a higher degree of failure in relation to enamel bond 2 . On the other hand, some studies showed no negative effects on ceramic surface, since the most failures was adhesive between the bonding material and the ceramic surface [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations